Polyoxymethylene Dimethyl Ethers from Methylal and Trioxane over Modified Cation-Exchange Resin - Zhang, Jianqiang; Tang, Bin; Fang, Dingye; Liu, Dianhua (Asian Journal of Chemistry, 2014)
Polyoxymethylene dimethyl ethers can increase cetane number and improve combustion efficiency when added to diesel fuel. Although intermittent reaction of polyoxymethylene dimethyl ethers synthesized from methylal and trioxane in a batch reactor has been known, the continuous reaction process for the synthesis of polyoxymethylene dimethyl ethers is still been pursued. The present work gives an overview of continuous process for the synthesis of polyoxymethylene dimethyl ethers from methylal and trioxane. The acidic cation-exchange resin modified by para-toluenesulfonic acid was used as catalyst for this process. The prepared catalysts were characterized by using several techniques such as BET, NH3-TPD and SEM. The analytical results of NH3-TPD reveal that the modified catalyst exhibited stronger acidity and less acidic sites than untreated catalyst. A relationship between catalytic performance in polyoxymethylene dimethyl ethers formation and the acid properties of catalyst is found. Their catalytic performance was assessed in a fixed-bed micro-activity test unit in a broad experiment range (temperature, residence time, pressure). The modified catalyst of acidic cation-exchange resin with 20 wt. % para-toluenesulfonic loading showed the highest performance. The modified catalyst presented significantly higher activity at 343 K. The methylal conversion was increased from 38.76 to 48.84 % with the increased of pressure from 0.5 to 2.0 MPa. Residence time analysis showed that the modified catalyst is stable at 20 min reaction time. The appropriate reaction conditions are temperature 343 K, pressure 2 MPa and residence time 20 min.